STRATEGI PEMASARAN PAKET WISATA PADA PT. PANDAWA LIMA TOUR AND TRAVEL INDONESIA DI DENPASAR - I Gede Adhi Suputra Arimbawa PG.; I GPB. Sasrawan Mananda; I Putu Sudana (Jurnal IPTA (Industri Perjalanan Wisata), 2014)
This research is about the marketing strategies implemented by PT. Pandawa Lima Tour and Travel tour packages. Company offers tour packages in Bali and beyond Bali tour packages with variety of facilities. As a common general company, PT. Pandawa Lima Tour and Travel has the objective to make profit and trying to satisfy consumers. This research aims to determine the marketing strategy package in PT. Pandawa Lima Tour and Travel tour package in Denpasar. The data collection method in research carried out by the method of observation, in-depth interviews, library research, and technique documentation. The data analysis technique used is descriptive qualitative combined with the SWOT approach. Discussion of the results of the marketing strategy adopted by the PT. Pandawa Lima Tour and Travel is SO strategy by increasing sales promotion to target markets, enhance cooperation with hotels and travel agents and maintain the diversity and innovation of product and service quality. ST strategies to further enhance cooperation with other travel agencies, and improve service quality. WO strategies to enhance the promotion through the mass media, and printing brochures, expanding market segments and improve the quality of human resources in education and training. While WT strategy by increasing promotional activities and improve human resources. Based on the results of the discussion, can give advice - advice on marketing strategies in PT. Pandawa Lima Tour and Travel tour packages that maintain good relations with the company's existing transport and suggest PT. Pandawa Lima Tour and Travel to their own transport, improving education and training for employees and appropriate compensation, as well as updating the architecture buildings and office equipment.